2020
DOI: 10.1002/ejp.1647
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiological nature of sarcomeres in trigger points in patients with myofascial pain syndrome: A preliminary study

Abstract: Musculoskeletal pain is a major cause of human suffering worldwide, with a prevalence between 13.7% and 47% among the global population (Bergman et al., 2001; Cimmino, Ferrone, & Cutolo, 2011). Myofascial pain syndrome (MPS) is one of the most common types of musculoskeletal pain. The presence of myofascial trigger points (MTrPs) is necessary for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 45 publications
0
29
0
5
Order By: Relevance
“…The procedure used to recruit MPS patients (M group) and healthy controls (C group) was described in previous publications. 13 Patients with MTrPs were recruited for the study at the orthopaedics department of Qilu Hospital at Shandong University, Jinan, China. Eleven participants were recruited into the M group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure used to recruit MPS patients (M group) and healthy controls (C group) was described in previous publications. 13 Patients with MTrPs were recruited for the study at the orthopaedics department of Qilu Hospital at Shandong University, Jinan, China. Eleven participants were recruited into the M group.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the sample biopsy procedure is provided in our previous publication. 13 Briefly, biopsies from the MTrPs were obtained using a disposable SuperCoreTM Biopsy instrument (ARGON) according to the international consensus on diagnostic criteria established in 2017. 5 The tissues were rapidly frozen in liquid nitrogen and stored at -80 C. The expression of proteins was measured using the RayBio Human Phosphorylation Array Kit (catalogue no.…”
Section: Sample Collection and Proteomic Analysismentioning
confidence: 99%
“…The substances can sometimes spread to adjacent spinal cord segments and cause referred pain characterized by MTrPs[ 17 ]. The central pain sensitization can increase the excitability of neurons and the expansion of the neuronal receptive fields causing refractory referred pain[ 18 ]. Alternatively, Stecco et al [ 19 ] suggested that muscular fascia, a form of connective tissue, may undergo pathological change under overload and damage leading to the biomechanical change of muscles and eventually to the reduction of contraction force and flexibility of muscles[ 20 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…В последнее время получила развитие теория, предполагающая наличие положительной обратной связи поддержания МТТ на молекулярном уровне по причине дизрегуляции специфических белков [24]. В настоящее время известно, что тирозин-киназный рецептор (receptor tyrosine kinases, RTK) и Rho-киназы участвуют в процессе Ca 2+ -чувствительного мышечного сокращения.…”
unclassified
“…С помощью секвенирования и РНК-анализа в области МТТ подтверждена дизрегуляция данного сигнального пути, обеспечивающего мышечное сокращение. Оказалось, что по сравнению с контрольной группой наблюдается значительное нарушение регуляции 15 белков из семейства RTK в виде увеличения активности, а также снижения функции двух белков из семейства RTK, сопровождающееся частичным повышением экспрессии EphB1/EphB2 на мембранах мышечных клеток, в которых присутствуют аномально сокращенные саркомеры [24].…”
unclassified